2009
DOI: 10.1080/09687630802697685
|View full text |Cite
|
Sign up to set email alerts
|

Injecting drug use and unstable housing: Scope for structural interventions in harm reduction

Abstract: Evidence links unstable housing, and especially homelessness, with elevated health harm among drug users, including riskier drug injecting practices. We undertook 45 in-depth qualitative interviews with injecting drug users (IDUs) in Bristol and London in 2006. IDUs were recruited through drug user networks and drug agencies. Temporary accommodation and hostels for the homeless may provide a 'safe haven' from street-based drug use and public injecting environments, and are characterised as a retreat from the '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 65 publications
(89 reference statements)
4
40
1
Order By: Relevance
“…The possibility exists for unintended harmful consequences for residents of housing programs that do not require abstinence. For example, Briggs et al (2006) found that injection drug users residing in a hostel in the United Kingdom reported that although the hostel provided them a safe and stable place to live, it also constituted a ''risk environment'' where residents experienced harassment and victimization by other residents and reported the formation of drug networks that they felt resulted in more harm for some residents. In other words, for some residents the program provided a refuge, but for others the residence was actually a harmful environment.…”
Section: Clarify What Constitutes Harm Reduction and Support Its Effementioning
confidence: 97%
“…The possibility exists for unintended harmful consequences for residents of housing programs that do not require abstinence. For example, Briggs et al (2006) found that injection drug users residing in a hostel in the United Kingdom reported that although the hostel provided them a safe and stable place to live, it also constituted a ''risk environment'' where residents experienced harassment and victimization by other residents and reported the formation of drug networks that they felt resulted in more harm for some residents. In other words, for some residents the program provided a refuge, but for others the residence was actually a harmful environment.…”
Section: Clarify What Constitutes Harm Reduction and Support Its Effementioning
confidence: 97%
“…However, I can't be sure because he continued to exercise intimidation and hostility over others in the same social space; this is, after all, the brutal world of STUs who practically live by dictions of violence and victimisation (Bourgois, 1995). However, although Cuz wanted me to understand how frustrated people like him were, his enthusiasm started to dissipate as the pressures of the street drug scene intervened on his intentions to stay clean in the hostel (Briggs et al, 2009). This was further exacerbated when relations evolved with Babe, the hostel kicked him out and his anger seemed to intensify.…”
Section: Discussion: Critical Reflectionsmentioning
confidence: 99%
“…In other research, I have documented the kind of volatile relations which exist between drug users residing in temporary accommodation (Briggs et al, 2009). Quite often, the most vulnerable are victimised and become the prey for other residents.…”
Section: Cuz and The Hostel Residentsmentioning
confidence: 99%
“…Although research has shown that housing plays an important and direct role in the prevention of hiv and other health-related harms among idu (Briggs et al 2009), policy-makers in Canada have failed to implement housing interventions as central tenets of current hiv/aids strategies for this population. In order to more effectively influence the development of evidence-based policy and programs that benefit equivocally housed drug users, scientists, policy-makers and service providers must promote rigorous housing-focused research, articulate why housing and hiv/aids issues are closely linked and justify how the provision of supportive housing can improve the health of drug users living with hiv/aids (Aidala and Sumartojo 2007).…”
Section: Homelessness and The Risk Environmentmentioning
confidence: 99%
“…In Canada, some housing programs have adopted a 'client-centred' harm reduction approach, which focuses on supporting individuals in meeting their housing, substance abuse and health care needs in a flexible, respectful and dignified way (Evans and Strathdee 2006). The provision of housing is increasingly viewed internationally as an evidence-based harm reduction strategy to reduce risk behaviour and prevent adverse health outcomes among people who inject drugs (Briggs et al 2009). Evidence also exists to suggest that idu who achieve stable housing are more likely to cease injection drug use altogether and are less likely to relapse (Shah et al 2006).…”
Section: Housing Firstmentioning
confidence: 99%